Analysis of Service Quality on Patient Satisfaction at the Small Bridge Health Center, Bengkulu Province - Fery Surahman Saputra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The purpose of this study was to determine what factors are related to the quality of Puskesmas services with the level of patient satisfaction. In this case, of course, it will provide enormous benefits for the internal health office, especially the Bengkulu Provincial Health Office, in improving the quality of health services for patients, especially general patients at the Jembatan Kecil Health Center in Bengkulu Province. The type of research used is survey research, namely research that uses a sample from a population, questionnaires are used as a data collection tool (Singarimbun and Effendi, 1999). In this study, data was collected by means of a questionnaire, then the questionnaire was distributed to respondents. The distribution of questionnaires is usually carried out to obtain existing data or facts and to seek actual information that can support this research. Physical evidence, reliability, responsiveness and empathy are variables used in the study. Multiple correlation analysis to determine the degree or strength of the relationship between all independent variables (X) to the dependent variable (Y) simultaneously. By using the SPSS program, a multiple correlation value was obtained between the independent variables (reliability, responsiveness, assurance, empathy and physical evidence) to the dependent variable (patient satisfaction) of 0.827, meaning the relationship between the independent variables (reliability, responsiveness, assurance, empathy and physical evidence) ) to the dependent variable (patient satisfaction) with a very close category.